Notes, Notation, Narration : Le carnet de terrain comme « carto-ethnographie » - Carole Lanoix (Belgeo)
How do we account for perceived, built and lived space in cities, without reducing the complexity of approaches, systems and practices? This is a challenge of the in situ observation, which is a product of changing the ability to confront our bodies to one of the place realities, particularly the one that constructs the urban “small things” where walking is both one of its means and one of its components. Looking for a metric that would be pedestrian, every step counts and participates in the cities’ spaces of representation. Based on the cartographic knowledge coming from the past, from the other cultures and from the contemporary art, walking, as an exploration of the world, sets up a collection of traces in the form of mapping stories. Embarked in its journey, the notebook questions the notion of fieldwork, in the form of researcher’s “ethnonishment” report. From the space of representation to the representation of space, it is the object of a mapping process to be (re)invented. The “carto-ethnography” in gestation is delineated through the collection of notes and by creation of a notation whose purpose is narration by a map.